Marginal Bone Levels and Trabecular Bone Structure: A Longitudinal Population Study of women - Jonasson Grethe; Ahlqwist Margareta (Journal of Aging Research And Healthcare, 2016)
Bone quality is difficult to assess but the skeletal bone condition is reflected in mandibular trabecular bone, which is well imaged in periapical dental radiographs. The aim of this 12-year prospective cohort study was to test if marginal mandibular bone loss differs in women with varying trabecular bone structure. The sample consisted of 460 women (aged 38, 46, and 54 years) from the prospective population study of women in Gothenburg, Sweden. Marginal bone loss was assessed according to a five-graded scale in two surveys 12 years apart, and the mandibular bone structure was evaluated visually as sparse, mixed, and dense. The results showed that marginal bone loss was significantly correlated to mandibular bone structure (r= 0.20; p<0.001 at baseline, and r= 0.17; p<0.001 after 12 years). Significant differences in marginal bone loss between trabeculation groups were found, with the largest loss in the group with dense trabeculation. Age, smoking, number of missing teeth and trabecular bone structure explained 20-28% of the variation in marginal bone loss. The conclusion was that women with dense trabecular bone in the mandible suffered a stronger periodontal bone destruction when negative events occur, than the women with sparser trabeculation.
Keywords: Bone